Karl Barth's Theology and Its Implications for Christian Ethics - Lesnussa, Absalina Lusia (CV. Publikasi Indonesia, 2025)
This article examines Karl Barth's theology with a focus on the implications of that theology for modern Christian ethics. Barth affirms the sovereignty of God and Revelation as the primary basis of ethics, rejects secular ethics, and emphasizes social and moral responsibility rooted in a relationship with God. The implications include Christian ethical acts that are oriented towards obedience as well as social responsibility in the context of the contemporary world.